QR code advertising: A cross-country comparison of Turkish and German consumers - (:unkn) unknown (Inderscience Publishers, 2018)
Among various mobile-based communication technologies, QR codes have recently gained a great popularity in mobile advertising. These codes are used by marketers for advertising in various ways such as in print media, in outdoor advertising, or even on the product packages so that consumers could get relevant information at instance. In the current literature perceived usefulness, behavioural intention, previous experience, knowledge and environmental constraints have been identified as the factors that lead consumers to scan QR code ads. The aim of this study was to investigate the factors and their extent in influencing the QR code ad scanning behaviour of Turkish and German consumers. The results demonstrate that perceived usefulness and previous experience affect the scanning behaviour of both the groups, whereas knowledge about scanning and environmental constraints affects only the scanning behaviour of Turkish consumers. Contrary to our expectations, behavioural intention does not influence the behaviour of either Turkish or German consumers. Copyright © 2018 Inderscience Enterprises Ltd.
Keywords: Advertising; German consumers; IBM; Integrated behavioural model; QR code; Turkish consumers